2013
DOI: 10.1186/2040-2392-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autism in mainland China, Hong Kong and Taiwan: a systematic review and meta-analysis

Abstract: BackgroundThe prevalence of autism spectrum conditions (ASC) is 1% in developed countries, but little data are available from mainland China, Hong Kong and Taiwan. This study synthesizes evidence relating to the prevalence of ASC in these areas and assesses the effects of research methodology on prevalence estimates.MethodsSystematic literature searches were conducted in PubMed, Web of Knowledge, China Web of Knowledge and Weipu databases, as well as relevant papers published from 1987 to 2011, reporting preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
115
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 51 publications
(72 reference statements)
1
115
4
2
Order By: Relevance
“…However, the Hong Kong Government's estimation of the prevalence rate of ASD was on the low side (The Rehabilitation Advisory Committee, 2005). Based on a metaanalytic study, Sun et al (2013) concluded that there was a potential underdiagnosis and underdetection of ASD in Chinese societies. It has also been argued that the available studies suffered methodological weaknesses, such as small sample size, divergent conceptual principles, and inconsistent measurement tools (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Hong Kong Government's estimation of the prevalence rate of ASD was on the low side (The Rehabilitation Advisory Committee, 2005). Based on a metaanalytic study, Sun et al (2013) concluded that there was a potential underdiagnosis and underdetection of ASD in Chinese societies. It has also been argued that the available studies suffered methodological weaknesses, such as small sample size, divergent conceptual principles, and inconsistent measurement tools (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a metaanalytic study, Sun et al (2013) concluded that there was a potential underdiagnosis and underdetection of ASD in Chinese societies. It has also been argued that the available studies suffered methodological weaknesses, such as small sample size, divergent conceptual principles, and inconsistent measurement tools (Sun et al, 2013). This has pointed to the need to use more advanced methods to study ASD in Chinese contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Sun et al assessed the prevalence of childhood autism in China including Hong Kong and Taiwan regions based on 18 epidemiological studies from 1987 to 2011. They estimated the pooled prevalence of autism in children as 11.8/10,000 in the Mainland of China and 26.6/10,000 in all of China [4]. In the same year, a meta-analysis of the studies (excluding the only nationwide study) reported a pooled estimated prevalence of ASD of 24.5/10,000 in the Mainland of China [5].…”
mentioning
confidence: 99%
“…Children suspected with developmental delay or ASD will be taken to our department for further assessment; (2) pediatricians in our department interview the parents to get the message of symptoms of concern and some basic information about the child's developmental history; (3) then the doctor may conduct a structured observation and apply some basic screening assessments on the child to evaluate whether the concerns are valid or not. (4) based on the screening results, if a red flag shows there are valid concerns, we will make an official diagnosis according to the diagnostic criteria or make an appointment for ADOS and/or ADI-R assessment if possible; (5) the children diagnosed with ASD will be assessed with other scales such as Psychological Educational Profile 3rd Edition (PEP-3) and Griffiths Development Scales Chinese Edition or Wechsler's Intelligence Scale IV to collect the information about the abilities of multi-domains. After assessments, we will discuss with the parents about the individual educational plan for their children.…”
mentioning
confidence: 99%
See 1 more Smart Citation